Oxidación microbiológica de alcoholes por Nocardia corallina B-276 - Pérez Méndez, Herminia Inés (Universidad Autónoma Metropolitana, 1998)
Oxidation is one of the main tools in the synthesis of organic compounds and it is also one of the methods with more potential for environmental pollution, for that reason new methodologies, as microbial oxidation, are always welcome. The main objective of this work is the determination of the scope and limitations of the microbial oxidation of alcohols by Nocardia coralha B-276; in order to do these 43 substrates were selected: 21 primary benzylic alcohols, 5 allylic alcohols, 4 heterocyclic alcohols, 4 aldehydes, 2-naftol, cis-verbenol and 7 diols, in a lmmol scale. For the primary benzylic alcohols, the products of the biotransformation were the corresponding carboxylic acids, with the exception one that produced the corresponding ketone, with yield ranging from 5 to 77 Oh. For the allylic alcohols tested, only two of them gave the carboxylic acid in yields around 25-57 %; the other three were not biotransformed. In the case of the heterocyclic compounds, only furfurilic alcohol was successfully oxidized to furoic acid in 51 % yield; the other three were not biotransformed. The aldehydes produced carboxylic acid in yield from 33 to 71 %. 2-naftol and cis-verbenol, non-structurally related to benzyl alcohol, were oxidized to the expected products in 19 and 71 % yield, respectively. For the diols only one produced the expected lactone in 42 % yield. All products were purified (by crystallization or chromatography) and characterized by: mp, IR and 'H-NMR spectroscopy (by cornparation with authentic samples). This work shows the versatility and limitations of the microbial oxidation of benzylic and allylic alcohols with Nocardia corallina B-276, as well as the viability of this methodology, because either the alcohol or the aldehyde can be used as starting materials, obtaining reproducible results. It also describes the initial work in the study of immobilization of the cells of Nocardia corallina B-276 with barium alginate and its application to the microbial oxidation described above. In these studies the furfurilic alcohol was used as substrate.; La oxidación en el campo de la química orgánica industrial constituye una de las principales herramientas en la síntesis de compuestos orgánicos y uno de los métodos con mayor potencial de contaminación, por lo anterior eventuales desarrollos de metodologías alternas como las oxidaciones microbiológicas siempre serán bienvenidas. El objetivo principal del presente trabajo es estudiar el espectro y alcance de la oxidación microbiológica de alcoholes por Nocardia corallina B-276. Se sometieron a la biooxidación 43 substratos con Nocardia corallina B-276, a una escala de 1 mmol; de los cuales, 21 fueron de alcoholes bencílicos primarios. El producto de dichas biotransformaciones fueron los ácidos carboxílicos correspondientes, y una cetona con rendimientos del 5 al 77 %. Por otro lado, de los 5 alcoholes alílicos solamente dos produjeron los ácidos, en rendimientos del 25 al 57 %; los tres restantes no fueron biotransformados. Dentro de los substratos 4 fueron heterocíclicos, de los cuales solo el alcohol furfurílico se oxido al ácido furoíco en un rendimiento del 51 Oh, y los otros tres no fueron biotransformados. También se incluyeron 4 aldehídos, en estos casos todos ellos produjeron los ácidos carboxílicos en rendimientos del 33 al 71 %. Entre los alcoholes no relacionados estructuralmente, el 2-naftilcarbinol y el cisverbenol produjeron los productos esperados en 19 y 71 % de rendimiento, respectivamente. De los 7 dioles que se probaron, soiamente uno de ellos produjo la lactona esperada en 42 YO de rendimiento. Todos los productos fueron purificados (cristalización o cromatografía) y caracterizados por: pf, espectroscopia de IR, RMN-’H (comparándolos con muestras estándar). Este trabajo muestra la versatilidad y limitaciones de la oxidación de alcoholes bencílicos y alílicos con la Nocardia coralina B-276 así como la viabilidad de ésta metodología, ya que se puede partir indistintamente del alcohol o del aldehído, conduciendo a resultados reproducibles. Además se describen estudios iniciales de la inmovilización de células de Nocardia corallina B-276 en alginato de bario y su utilización en la oxidación microbiológica descrita anteriormente, para estos estudios se uso al alcohol furfurílico como substrato.